Influence of shielding gas flow on the TIG welding process using stainless steel 304 material - Aljufri, Aljufri; Sofyan, Sofyan; Rizki, Muhammad Nuzan; Putra, Reza; Mawardi, Indra (Journal of Welding Technology, 2024)
A common issue encountered with main heat exchanger equipment is improper operation, which can lead to the development of cracks in the stainless-steel pipes. The welding process alters the metal microstructure in the heat-affected zone, thereby affecting the mechanical properties of the welded joint. To mitigate this issue, TIG welding with argon shielding gas is employed. This method helps prevent oxidation and ensures the formation of a stable welding arc in 304 stainless steel, which is renowned for its excellent mechanical properties and corrosion resistance. The objective of this study is to evaluate the impact of variations in shielding gas flow on the mechanical properties of 304 stainless steel plates during the TIG welding process. The aim is to determine the optimal settings for producing robust and long-lasting welded joints. To assess the hardness of the welded joints, we employed a Brinell-type Hardness Tester FB-3000LC machine. A Brinell steel ball indenter measuring 5 mm on the HBW scale and applying a load of 125 Kgf was utilized. At a protective gas flow rate of 8 L/min, the average tensile stress was 44.72 N/mm², strain was 0.177, modulus of elasticity was 2518 MPa, and hardness was 99.712 HBW. Increasing the gas flow rate to 13 L/min resulted in an average tensile stress of 47.50 N/mm², strain of 0.189, elastic modulus of 2525 MPa, and hardness of 105.522 HBW. Further increasing the gas flow rate to 18 L/min led to an average tensile stress of 49.69 N/mm², strain of 0.192, modulus of elasticity of 2597 MPa, and hardness of 106.704 HBW. Based on the research findings, it was observed that the weld area exhibited an increase in hardness values due to the heat generated during the welding process. The use of protective gas flow during welding is deemed effective in producing well-formed welded joints, as it prevents fractures from occurring within the weld area during the tensile test process. The choice of protective gas is determined by the dimensions of the material plate.